TEACHER MOTIVATION: REFLECTIONS ON THE IMPORTANCE OF YOUR TEACHING-LEARNING PROCESS (Fiep Bulletin - online, 2012)
In the process of teaching and learning is believed that teacher motivation is as fundamental to the success of its implementation. It is for the teacher to build a favorable environment, able to arouse students' interest and knowledge in the discipline, as well as keep them motivated to succeed in the educational activity. This study aimed to investigate the motivation and teacher variables that affect satisfaction with the profession and in the interest of learning and learners. It was found that teachers need to motivate their students to teach, and therefore, must also be motivated to investigate the factors influencing this interest and act upon them, issues such as: satisfaction with the profession, training and teacher training and barriers in the teaching-learning were identified by teachers as factors for motivation.
Keywords: motivation; teaching; learning.